Long Term Evolution of the Size Distribution of Portuguese Cities - Ana Paula Delgado; Isabel Maria Godinho (European Regional Science Association (ERSA), 2005)
In this paper we study the evolution of the Portuguese urban system from 1864 to 2001. We apply the rank-size model and use rank-size estimates to describe the evolution of city-size hierarchy. Non paretian behaviour of the distribution is examined by adding a quadratic term to the basic equation of the model. Our results enhance two different processes in the evolution of urban system: until the middle of the twentieth century urban growth was accompanied by population concentration in the largest cities and proliferation of small cities; afterwards growth benefits middle size cities, reinforced in the last decades by heavy population losses in the two largest cities. From the association between the characteristics and evolving pattern of city size distribution and the spatial pattern of urban growth, it appears that the non paretian behaviour of city size distribution in the last decades can be linked to the particular growth process of cities located in the proximity of the central cities of the two metropolitan areas of Portugal's mainland. In order to obtain a better understanding of the dynamics of the Portuguese urban system we examine the movements in the ranking of cities. We also analyse the existence of spatial correlation in the process of urban hierarchy restructuring.
Keywords: 330